MODELLING STUDY OF TEMPERATURE EFFECT ON THE EFFICIENCY OF INDUSTRIAL HYDROPURIFICATION PROCESS - TAHIR, MUHAMMAD HUZAIMI (IRC, 2017)
Hydropurification, or hydrotreating, is a process where hetero atoms such as sulfur, nitrogen, oxygen and metals are removed and carbon bonds such as olefinic and aromatic bonds are saturated. Hydropurification process is extensively utilized in the chemical/petrochemical industries and oil refineries. This paper focuses on the effect of temperature exclusively on the efficiency of the industrial hydropurification process through a modeling study. The modeling study involves the development of a mathematical model using industrial data, which is obtained from the hydropurification unit of a purified terephthalic acid production plant. Upon the development of the mathematical model, the model is to be inserted into MATLAB for compilation. By analyzing the removal of the main impurity in the system, 4-carboxybenzaldehyde (4-CBA), the operating conditions can be manipulated to fulfill the impurity reduction more efficiently. In this stage, a sensitivity analysis is conducted to ensure that the mathematical model developed responds to changes in the values of parameters and variables. From the analysis, it can be concluded that the solubility of hydrogen decreases as temperature increases by observing the concentration of hydrogen in terephthalic acid over a range of temperature. Due to the reduction of solubility of hydrogen in terephthalic acid, the concentration of 4-CBA also increases with increasing temperature. The trend can also be explained by the increase in value of Henry’s Law constant with increasing temperature. The most accurate model to develop the system, upon comparing with the experimental data provided by the industry, is by using the plug flow model. This is due to a small error percentage of 1.75%, in comparison to the CSTR model with an error percentage of 19.30%. Further studies can examine the effect of catalyst deactivation and the side reactions that occur in the dehydrogenation reaction to obtain a more representative result.